2019
DOI: 10.32479/ijeep.8279
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Management Accounting Systems in Influencing Environmental Uncertainty, Energy Efficiency and Environmental Performance

Abstract: The current investigation analyzes the role of energy efficiency (EEF) and environmental uncertainty in influencing environmental performance (EPR) of Malaysian small and medium enterprises. Our examination endeavors to add to existing studies in a few different ways. To begin with, we shed some light on the specific association that could exist between the utilization of management accounting system (MAS), perceived environmental uncertainty (PEU) and EEF. Furthermore, we look at the consequential impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…Modern businesses faced with broad uncertainty in terms of competition, scientific discoveries, strict regulations, technological advances, and environmental changes need to take advantage of an effective management accounting system so that business voters can make decisions to reduce environmental uncertainty. Therefore, the use of a management accounting system can help reduce the impact of environmental uncertainty [1]. The results of this study are in line with that conducted by Alaeddin et al, (2019) which states that there is a negative influence between the management accounting system on environmental uncertainty.…”
Section: The Management Accounting System Has a Negative Effect On Environmental Uncertaintysupporting
confidence: 90%
See 2 more Smart Citations
“…Modern businesses faced with broad uncertainty in terms of competition, scientific discoveries, strict regulations, technological advances, and environmental changes need to take advantage of an effective management accounting system so that business voters can make decisions to reduce environmental uncertainty. Therefore, the use of a management accounting system can help reduce the impact of environmental uncertainty [1]. The results of this study are in line with that conducted by Alaeddin et al, (2019) which states that there is a negative influence between the management accounting system on environmental uncertainty.…”
Section: The Management Accounting System Has a Negative Effect On Environmental Uncertaintysupporting
confidence: 90%
“…Environmental performance is one of the focuses of attention of stakeholders and investors in today's business world. Modern businesses are busy with inventive solutions to reduce their role in causing environmental pollution and nowadays economies around the world are starting to be interested in taking steps to improve environmental conditions by practicing environmentally friendly business methods [1]. The company wishes to be able to continue to produce and keep the environment in good condition, because the company's spirit is to fulfill its sustainable economic goals by maintaining profitability through strong internal awareness and maintaining environmental responsibility in the future [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation of their results can be attributed to the fact that they studied firms in China, which are generally more risk averse than Western firms and are more likely to avoid high-investment technology adoption. Furthermore, a wide variety of studies have reported an insignificant role of EU [73,74]. Despite this, contrary to those results and in accordance with the dominant view, Peltier et al [75] argued that small businesses facing high EU are more likely to adopt innovations.…”
Section: Perceived Eu and Erp Adoptionmentioning
confidence: 95%
“…The use of an appropriate environmental management accounting system helps to improve the environmental performance of business entities [23]. The role of accounting management systems in influencing environmental uncertainty and energy efficiency on economic and environmental performance of enterprises is becoming increasingly important in scientific research [24].…”
Section: Literature Reviewmentioning
confidence: 99%